Economic evaluation of weekends-off antiretroviral therapy for young people in 11 countries. Issue 5 (February 2018) - Tierrablanca, Luis Enrique; Ochalek, Jessica; Ford, Deborah; Babiker, Ab; Gibb, Diana; Butler, Karina; Turkova, Anna; Griffin, Susan; Revill, Paul
Abstract: Objectives: To analyze the cost effectiveness of short-cycle therapy (SCT), where patients take antiretroviral (ARV) drugs 5 consecutive days a week and have 2 days off, as an alternative to continuous ARV therapy for young people infected with human immunodeficiency virus (HIV) and taking efavirenz-based first-line ARV drugs. Methods: We conduct a hierarchical cost-effectiveness analysis based on data on clinical outcomes and resource use from the BREATHER trial. BREATHER is a randomized trial investigating the effectiveness of SCT and continuous therapy in 199 participants aged 8 to 24 years and taking efavirenz-based first-line ARV drugs in 11 countries worldwide. Alongside nationally representative unit costs/prices, these data were used to estimate costs and quality adjusted life years (QALYs). An incremental cost-effectiveness comparison was performed using a multilevel bivariate regression approach for total costs and QALYs. Further analyses explored cost-effectiveness in low- and middle-income countries with access to low-cost generic ARV drugs and high-income countries purchasing branded ARV drugs, respectively. Results: At 48 weeks, SCT offered significant total cost savings over continuous therapy of US dollar (USD) 41 per patient in countries using generic drugs and USD 4346 per patient in countries using branded ARV drugs, while accruing nonsignificant total health benefits of 0.008 and 0.009 QALYs, respectively. Cost-effectiveness estimates were similar across settings with access to generic ARV drugs but showed significant variation among high-income countries where branded ARV drugs are purchased. Conclusion: SCT is a cost-effective treatment alternative to continuous therapy for young people infected with HIV in countries where viral load monitoring is available. Abstract : Supplemental Digital Content is available in the text